Bereaved mothers’ attitudes regarding autopsy of their stillborn baby - H Odendaal; M Human; R Goldstein; C Groenewald; H Kinney (South African Medical Association, 2017)
Background. Here we present additional information from the Safe Passage Study, where the effect of alcohol exposure during pregnancy on sudden infant death syndrome and stillbirth was investigated. Objective. To explore bereaved mothers’ attitudes toward obtaining an autopsy on their stillborn baby, and the future implications of consenting or non-consenting to autopsy in retrospect. Methods. Demographic data was obtained by a questionnaire. A largely qualitative mixed-methods approach was used to meet the aims of the study, using an exploratory and descriptive research design to provide a detailed description of maternal attitudes. A semi-structured questionnaire based on information from literature and reflections on practice was administered during individual interviews. Results. We interviewed 25 women who had had a recent stillbirth. The time interval between the time of consenting to autopsy and completing this study ranged from 6 to 18 months. Most participants reported that autopsy results provided peace of mind and helped alleviate their feelings of blame. Participants who were unable to comprehend the results reported negative reactions to receiving autopsy results. The majority of participants were of the opinion that they benefited from consenting to autopsy. Conclusion. Autopsy and the disclosure of its results generally contribute positively to coping following stillbirth.